A retrospective cohort study on the provision and outcomes of pharmacological therapy after revascularisation for peripheral arterial occlusive disease: a study protocol. Issue 1 (27th January 2020) - Peters, Frederik; Kreutzburg, Thea; Kuchenbecker, Jenny; Debus, Sebastian; Marschall, Ursula; L'Hoest, Helmut; Behrendt, Christian-Alexander
Abstract : Background: Symptomatic peripheral arterial occlusive disease (PAOD) involves highly complex and costly revascularisations for preventing adverse limb events and impaired survival. Contrary to recommendations from valid guidelines, a large group of patients do not receive adequate pharmacological therapy after such interventions. Based on health insurance claims data, our study aims to assess (1) the extent of provision of pharmacological therapy after revascularisation and (2) related long-term outcomes for all patients and subgroups, that is, gender and disease severity. Methods: A retrospective observational population-based cohort study will be based on data from the second largest statutory health insurance fund in Germany (BARMER) covering about 13% of the insured population ( 10 million patients). Study entry is the index revascularisation for symptomatic PAOD. Study variables will be analysed and compared among subgroups using parametric and non-parametric tests, generalised linear regression analysis and survival models. Discussion: This study will provide a comprehensive insight in the extent and time trends of adequate provision of pharmacological therapy and long-term outcomes for patients with symptomatic PAOD. This may help to identify those patients benefiting most from improved pharmacological therapy for increasing the success of revascularisations in general. Trial registration: NCT03909022 .